Quran Criticism, the Historical-Critical Method, and the Secularization of Biblical Theology - Eskola, Timo (Journal of theological interpretation, 2010)
The emergence of historical criticism of the Bible was partly influenced by medieval Quran criticism. This background was still well known in the 19th century but was later forgotten when emphasis was laid on Greek literature. Scholars such as Riccoldo da Monte di Croce had written critical works against the Quran. This tradition reemerged 200 years later in Germany when Martin Luther translated Riccoldo's Confutatio Alcorani. The special features in Riccoldo's work are the criteria he used hoping to prove that the Quran was not divine revelation. The famous Deist Hermann Reimarus later demanded that the Bible be read in the same way as other literature. His examples in Wolfenbüttel Fragments are mostly taken from the Quran. Reimarus adopted Riccoldo's criteria when interpreting the Bible. The purpose of his rationalistic criticism was to show that contradictions, inconsistencies, and lies prove that, as with the Quran, neither can the Bible be held as divine revelation. Reimarus, in his apology "for the Rational Reverers of God," stated that Christian doctrines are based on a fraud because the apostles created the whole Systema only after Jesus' death. Jesus' original proclamation was political. This dichotomy, confirmed later in David Strauss's biography on Reimarus, became the basis for the criterion of dissimilarity in NT interpretation. Rudolf Bultmann then gave this criterion its present formulation, and it is still used, for instance, by the Jesus Seminar.